Экспериментальный и численный анализ свободных колебаний пологой оболочки - Чешко, Ксения Федоровна; Аврамов, Константин Витальевич; Полищук, Олег Федорович (НТУ "ХПИ", 2017)
Получена модель с конечным числом степеней свободы, описывающая свободные колебания пологой оболочки. Для вывода этой динамической системы применяется метод Рэлея-Ритца и энергетический подход Лагранжа. Для аппроксимации коле- баний использовались В-сплайны. Рассмотрена сходимость собственных частот, определены внутренние резонансы. Проведен эксперимент с возбуждением свободных и вынужденных колебаний оболочки, подтверждающий результаты расчета. Для экспериментального определения форм колебаний оболочки возбуждались ее вынужденные колебания с помощью кинематического движения заделки. Кроме амплитуд для построения форм колебаний измерялись фазовые сдвиги между ко- лебаниями в опорной точке и колебаниями в остальных точках. Представлены таблицы для сравнения результатов расчета и эксперимента для собственных форм и собственных значений.

A model with the finite number of degrees of freedom was obtained, which describes free oscillations of a shallow shell. To derive this dynamical system, the Rayleigh-Ritz method and Lagrange's energy approach were applied provided that the deformations and displacements are related by the Cauchy relations. B-splines were used to approximate the oscillations. The convergence of natural frequencies was considered, for which calculations were made for a different number of basis functions in the expansion of the modes of oscillations. Internal resonances that significantly affect the nonlinear deformation of the structure are determined. The experiment was performed with excitation of free and forced oscillations of the shell, which confirms the results of the calculation. For the experimental determination of the modes of oscillation of the shell, its forced oscillations were excited with the aid of the kinematic motion of the embedding. Tables are presented for comparing the results of calculation and experiment for eigenmodes and eigenvalues.
Experimental and numerical analysis of free shallow shell oscillations
Keywords: оболочечные конструкции; В-сплайны; собственные значения; собственные формы; B-splines; eigenvalues; eigenmodes